Sports Massage for Muscle Injury Rehabilitation: A PRISMA-Based Systematic Review - Senia Mariana Sinaga; Muhammad Azkar Saleh; Daphne Rudi Silalahi (IGI Active Living and Health Insight, 2026)
Purpose of the study: This systematic review aims to evaluate the effectiveness of sports massage therapy in the rehabilitation of muscle injuries, examining its impact on pain reduction, functional recovery, range of motion, and return-to-activity timelines. The study synthesizes current evidence to provide clinical recommendations for practitioners and identify areas requiring further investigation. Materials and methods: A comprehensive literature search was conducted across PubMed, Scopus, Web of Science, CINAHL, and Cochrane Library databases from inception to September 2024. The review followed PRISMA 2020 guidelines and included randomized controlled trials (RCTs), quasi-experimental studies, and cohort studies examining sports massage interventions for acute and chronic muscle injuries. Two independent reviewers screened 1,847 records, with 23 studies meeting inclusion criteria for qualitative synthesis and 15 for quantitative analysis. Data extraction focused on intervention characteristics, outcome measures, pain scales, functional assessments, and adverse events. Results: The analysis included 23 studies encompassing 1,456 participants with various muscle injuries (strains, contusions, delayed onset muscle soreness). Sports massage demonstrated significant improvements in pain reduction (mean difference: -1.8 points on VAS, 95% CI: -2.3 to -1.3, p<0.001), enhanced range of motion (mean increase: 12.4°, 95% CI: 8.7 to 16.1, p<0.001), and accelerated functional recovery compared to passive rest or standard care. Optimal treatment protocols involved 2-3 sessions per week for 15-30 minutes during acute phases, transitioning to maintenance protocols. No serious adverse events were reported. Heterogeneity in massage techniques, injury types, and outcome measurement tools was noted across studies. Conclusions: Sports massage represents an effective, safe adjunct therapy for muscle injury rehabilitation, demonstrating clinically significant improvements in pain management, functional restoration, and recovery acceleration. Evidence supports its integration into comprehensive rehabilitation programs, particularly when combined with therapeutic exercise and progressive loading protocols. Future research should standardize intervention protocols, establish optimal dosing parameters, and investigate long-term outcomes and injury prevention effects.